Improved iron acquisition of Astragalus sinicus under low iron-availability conditions by soil-borne bacteria Burkholderia cepacia - Cheng Zhou; Lin Zhu; Zhongyou Ma; Jianfei Wang (Journal of Plant Interactions, 2018)
Soil bacteria can assist plant growth and increase uptake of nutrient elements, the question arises as to whether beneficial soil microbes confer augmented iron (Fe) content of host plants under Fe limited conditions. Herein, a novel strain of Burkholderia cepacia (strain JFW16) was isolated from rhziospheric soils of Astragalus sinicus grown under alkaline conditions. Inoculation of plants with B. cepacia JFW16 displayed increased endogenous Fe content compared with non-inoculated plants. Growth promotion and enhanced photosynthetic capacity were also observed for the inoculated plants. The inoculation with JFW16 significantly increased the rhizospheric acidification, and up-regulated the transcription of some Fe acquisition-associated genes in Astragalus sinicus. Moreover, the metabolic pathways of flavins were remarkably enhanced in the inoculated plants, showing the increased biosynthesis and release of flavins in roots. Collectively, these findings demonstrated the potential of B. cepacia JFW16 to improve Fe assimilation in agricultural crops.